Panitumumab plus radiotherapy versus chemoradiotherapy in patients with unresected, locally advanced squamous-cell carcinoma of the head and neck (CONCERT-2): a randomised, controlled, open-label phase 2 trial. Issue 2 (February 2015) - Giralt, Jordi; Trigo, Jose; Nuyts, Sandra; Ozsahin, Mahmut; Skladowski, Krzysztof; Hatoum, Georges; Daisne, Jean-Francois; Yunes Ancona, Alejandro César; Cmelak, Anthony; Mesía, Ricard; Zhang, Alicia; Oliner, Kelly S; et al.
Summary: Background: We aimed to compare panitumumab, a fully human monoclonal antibody against EGFR, plus radiotherapy with chemoradiotherapy in patients with unresected, locally advanced squamous-cell carcinoma of the head and neck. Methods: In this international, open-label, randomised, controlled, phase 2 trial, we recruited patients with locally advanced squamous-cell carcinoma of the head and neck from 22 sites in eight countries worldwide. Patients aged 18 years and older with stage III, IVa, or IVb, previously untreated, measurable (≥10 mm for at least one dimension), locally advanced squamous-cell carcinoma of the head and neck (non-nasopharygeal) and an Eastern Cooperative Oncology Group performance status of 0–1 were randomly assigned (2:3) by an independent vendor to open-label chemoradiotherapy (two cycles of cisplatin 100 mg/m 2 during radiotherapy) or to radiotherapy plus panitumumab (three cycles of panitumumab 9 mg/kg every 3 weeks administered with radiotherapy) using a stratified randomisation with a block size of five. All patients received 70–72 Gy to gross tumour and 54 Gy to areas of subclinical disease with accelerated fractionation radiotherapy. The primary endpoint was local-regional control at 2 years, analysed in all randomly assigned patients who received at least one dose of their assigned protocol-specific treatment (chemotherapy, radiation, or panitumumab). The trial is closed and this is the final analysis. This study is registered withClinicalTrials.gov, numberNCT00547157 . Findings: Between Nov 30, 2007, and Nov 16, 2009, 152 patients were enrolled, and 151 received treatment (61 in the chemoradiotherapy group and 90 in the radiotherapy plus panitumumab group). Local-regional control at 2 years was 61% (95% CI 47–72) in the chemoradiotherapy group and 51% (40–62) in the radiotherapy plus panitumumab group. The most frequent grade 3–4 adverse events were mucosal inflammation (25 [40%] of 62 patients in the chemoradiotherapy group vs 37 [42%] of 89 patients in the radiotherapy plus panitumumab group), dysphagia (20 [32%] vs 36 [40%]), and radiation skin injury (seven [11%] vs 21 [24%]). Serious adverse events were reported in 25 (40%) of 62 patients in the chemoradiotherapy group and in 30 (34%) of 89 patients in the radiotherapy plus panitumumab group. Interpretation: Panitumumab cannot replace cisplatin in the combined treatment with radiotherapy for unresected stage III–IVb squamous-cell carcinoma of the head and neck, and the role of EGFR inhibition in locally advanced squamous-cell carcinoma of the head and neck needs to be reassessed. Funding: Amgen.